Price Analysis and Product Reviews on Online Shopping Decisions - Rusniati, Rusniati; Haq, Ahsanul (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This study aims to analyze the effect of prices and product reviews simultaneously on online shopping decisions. Then also analyze the effect of price partially on online shopping decisions and analyze the effect of product reviews partially on online shopping decisions. The population in this study are consumers who have done online shopping. The number of samples is 100 people. The sample technique was purposive sampling and the data analysis technique used multiple linear regression. The results of the study show that price and product reviews have a simultaneous effect on online shopping decisions. Partially, price influences online shopping decisions and product reviews influence online shopping decisions.